Health Implications of Low Vegetables and Local Gin Consumption amongst the Elderly in Ugheli, Delta State, Nigeria - Okadigwe John Chukwujekwu (Britain International of Exact Sciences (BIoEx) Journal, 2023)
The study delves into the critical topic of dietary habits and alcohol consumption patterns among the elderly in Ugheli, Delta State, Nigeria. This investigation aims to shed light on the health implications of low vegetable consumption and local gin intake within this aging population. The research addresses the pressing issue of the health and well-being of the elderly in Ugheli, Delta State. Specifically, it focuses on two critical problems: low vegetable consumption and excessive local gin consumption. These issues are of concern due to their potential adverse effects on the health of older adults. Local gin consumption may stem from cultural practices and limited understanding of its health risks. To address these problems, a survey research approach was employed. The sample size included 375 retirees from various communities within Ugheli. This sample size was determined using a stratified non-proportional sampling method. The research findings revealed that low vegetable consumption was associated with health risks such as weight gain, digestive problems, goiter, increased cancer risk, and various chronic conditions. Local gin consumption among the elderly was linked to poor coordination, central nervous system depression, excessive appetite, excessive urination, and low blood glucose levels. This research carries significant implications for the elderly population in Ugheli, Delta State. By highlighting the health risks associated with low vegetable consumption and excessive local gin intake, it underscores the need for tailored interventions, education programs, improved access to fresh produce, and cultural sensitivity in healthcare approaches. Ultimately, this study aims to improve the overall health and quality of life of older adults in the region.